Human Factors Guidelines for Road Systems - Collection C: Chapters 16, 17, 18, 19, 20, 22 (Tutorials 4, 5, 6), 23 (Updated), 24, 25, 26 (Updated) - Transportation Research Board; Transportation Research Board (The National Academies Press, 2010)
TRB's National Cooperative Highway Research Program (NCHRP) Report 600C, Human Factors Guidelines for Road Systems, Collection C--including Chapters 16, 17, 18, 19, 20, 22 (Tutorials 4, 5, 6), 23 (Updated), 24, 25, 26 (Updated)--explores human factors principles and findings for consideration by highway designers and traffic engineers. The report is designed to help the nonexpert in human factors to consider more effectively the roadway user's capabilities and limitations in the design and operation of highway facilities. NCHRP Report 600A (Chapters 1 through 5, 10, 11, 13, 22 [Tutorials 1 and 2], 23, and 26); and NCHRP Report 600B (Chapters 6, 22 [Tutorial 3], and 23 [Updated]) are available online. Additional chapters, to be developed under NCHRP Project 17-41 according to the priorities established by the project panel, are expected in late 2010.
Keywords: Transportation and Infrastructure

Recommended Guidelines for the Collection and Use of Geospatially Referenced Data for Airfield Pavement Management - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2010)
TRB’s Airport Cooperative Research Program (ACRP) Report 39: Recommended Guidelines for the Collection and Use of Geospatially Referenced Data for Airfield Pavement Management offers recommended guidelines for the collection and use of geospatially referenced data for airfield pavement management.The guidelines provide a data schema, data collection methods, data quality requirements, and other relevant information required for developing specifications and standards for integrating geospatial data into pavement management systems. Appendixes A through C to ACRP Report 39 are available online. Titles of the appendixes are as follows:• Appendix A: Survey Questionnaire• Appendix B: Questionnaire Responses• Appendix C: Pavement Management Systems Software Data Elements
Keywords: Transportation and Infrastructure

CNS Clinical Trials: Suicidality and Data Collection: Workshop Summary - Institute of Medicine (The National Academies Press, 2010)
The Food and Drug Administration (FDA) now requires that all clinical trials for drugs that affect the central nervous system—including psychiatric drugs—are assessed for whether that drug might cause suicidal ideation or behavior. The Institute of Medicine's (IOM) Forum on Neuroscience and Nervous System Disorders hosted a meeting on June 26, 2009, to discuss the FDA's new policy and how to analyze best whether suicidal thoughts predict actual suicidal behavior in the near future.
Keywords: Health and Medicine

Performance Measurement and Outcomes - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2010)
TRB’s Transit Cooperative Research Program (TCRP) Research Results Digest 95: Performance Measurement and Outcomes explores how performance measurements are used to achieve organizational goals and enhance quality of service at public transport planning, funding, and operating agencies in Hong Kong, Special Administrative Region of the People’s Republic of China; in the city-state of Singapore; in Kuala Lumpur, Malaysia; and in Taipei, Taiwan.
Keywords: Transportation and Infrastructure

Waste Forms Technology and Performance: Interim Report - National Research Council (The National Academies Press, 2010)
The Waste Forms Technology and Performance study examines requirements for waste form technology and performance in the context of the disposal system in which the waste will be emplaced. The Department of Energy, Office of Environmental Management requested this interim report to provide timely information for fiscal year 2011 technology development planning. The authoring committee has focused this interim report on opportunities associated with selected aspects of three components of its statement of task. These tasks are:
Keywords: Environment and Environmental Studies

Developing an Airport Performance-Measurement System - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2010)
TRB’s Airport Cooperative Research Program (ACRP) Report 19: Developing an Airport Performance-Measurement System provides guidance on developing and implementing an effective performance-measurement system for airports. The report’s accompanying CD-ROM provides tools designed to help users complete the step-by-step process for developing an airport performance-measurement system as presented in ACRP Report 19.The CD-ROM is also available for download from TRB’s website as an ISO image. Links to the ISO image and instructions for burning a CD-ROM from an ISO image are provided below.Help on Burning an .ISO CD-ROM Image Download the .ISO CD-ROM Image(Warning: This is a large file that may take some time to download using a high-speed connection.)
Keywords: Transportation and Infrastructure

The Impact of Genetically Engineered Crops on Farm Sustainability in the United States - National Research Council (The National Academies Press, 2010)
Since genetically engineered (GE) crops were introduced in 1996, their use in the United States has grown rapidly, accounting for 80-90 percent of soybean, corn, and cotton acreage in 2009. To date, crops with traits that provide resistance to some herbicides and to specific insect pests have benefited adopting farmers by reducing crop losses to insect damage, by increasing flexibility in time management, and by facilitating the use of more environmentally friendly pesticides and tillage practices. However, excessive reliance on a single technology combined with a lack of diverse farming practices could undermine the economic and environmental gains from these GE crops. Other challenges could hinder the application of the technology to a broader spectrum of crops and uses.
Keywords: Agriculture

A Methodology for Performance Measurement and Peer Comparison in the Public Transportation Industry - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2010)
TRB’s Transit Cooperative Research Program (TCRP) Report 141: A Methodology for Performance Measurement and Peer Comparison in the Public Transportation Industry explores the use of performance measurement and benchmarking as tools to help identify the strengths and weaknesses of a transit organization, set goals or performance targets, and identify best practices to improve performance.
Keywords: Transportation and Infrastructure

Data on Federal Research and Development Investments: A Pathway to Modernization - National Research Council (The National Academies Press, 2010)
Two surveys of the National Science Foundation's Division of Science Resources Statistics (SRS) provide some of the most significant data available to understand research and development spending and policy in the United States. These are the Survey of Federal Funds for Research and Development and the Survey of Federal Science and Engineering Support to Universities, Colleges, and Nonprofit Institutions. These surveys help reach conclusions about fundamental policy questions, such as whether a given field of research is adequately funded, whether funding is balanced among fields, and whether deficiencies in funding may be contributing to a loss of U.S. scientific or economic competitiveness.
Keywords: Behavioral and Social Sciences; Policy for Science and Technology; Surveys and Statistics

The Prevention and Treatment of Missing Data in Clinical Trials - National Research Council (The National Academies Press, 2010)
Randomized clinical trials are the primary tool for evaluating new medical interventions. Randomization provides for a fair comparison between treatment and control groups, balancing out, on average, distributions of known and unknown factors among the participants. Unfortunately, these studies often lack a substantial percentage of data. This missing data reduces the benefit provided by the randomization and introduces potential biases in the comparison of the treatment groups.
Keywords: Health and Medicine; Behavioral and Social Sciences; Surveys and Statistics

Guidance for Developing a Freight Transportation Data Architecture - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2010)
TRB’s National Freight Cooperative Research Program (NCFRP) Report 9: Guidance for Developing a Freight Transportation Data Architecture explores the requirements and specifications for a national freight data architecture to link myriad existing data sets, identifies the value and challenges of the potential architecture, and highlights institutional strategies to develop and maintain the architecture.The report also includes an analysis of the strengths and weaknesses of a wide range of data sources; provides information on the development of a national freight data architecture definition that is scalable at the national, state, regional, and local levels; and offers readers a better understanding of the challenges that might block the implementation of a national freight data architecture as well as candidate strategies for developing, adopting, and maintaining it.
Keywords: Transportation and Infrastructure

A Data-Based Assessment of Research-Doctorate Programs in the United States (The National Academies Press, 2010)
Doctoral education, a key component of higher education in the United States, is performing well. It educates future professors, researchers, innovators, and entrepreneurs. It attracts students and scholars from all over the world and is being emulated globally. This success, however, should not engender complacency.
Keywords: Policy for Science and Technology

Steps Toward Large-Scale Data Integration in the Sciences: Summary of a Workshop - National Research Council (The National Academies Press, 2010)
Steps Toward Large-Scale Data Integration in the Sciences summarizes a National Research Council (NRC) workshop to identify some of the major challenges that hinder large-scale data integration in the sciences and some of the technologies that could lead to solutions. The workshop was held August 19-20, 2009, in Washington, D.C.
Keywords: Health and Medicine

Improving State Voter Registration Databases: Final Report - National Research Council (The National Academies Press, 2010)
Improving State Voter Registration Databases outlines several actions that are needed to help make voter registration databases capable of sharing information within state agencies and across state lines. These include short-term changes to improve education, dissemination of information, and administrative processes, and long-term changes to make improvements in data collection and entry, matching procedures, and ensure privacy and security.
Keywords: Policy for Science and Technology; Industry and Labor; Behavioral and Social Sciences

Target-Setting Methods and Data Management to Support Performance-Based Resource Allocation by Transportation Agencies - Volume I: Research Report, and Volume II: Guide for Target Setting and Data Management - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2010)
TRB’s National Cooperative Highway Research Program (NCHRP) Report 666: Target Setting Methods and Data Management to Support Performance-Based Resource Allocation by Transportation Agencies - Volume I: Research Report, and Volume II: Guide for Target-Setting and Data Management provides a framework and specific guidance for setting performance targets and for ensuring that appropriate data are available to support performance-based decision-making.Volume III to this report was published separately in an electronic-only format as NCHRP Web-Only Document 154. Volume III includes case studies of organizations investigated in the research used to develop NCHRP Report 666.NCHRP Report 706: Uses of Risk Management and Data Management to Support Target-Setting for Performance-Based Resource Allocation by Transportation Agencies was released in 2011 and supplements NCHRP Report 666. NCHRP Report 706 describes how risk management and data management may be used by transportation agencies to support management target-setting for performance based resource allocation.
Keywords: Transportation and Infrastructure

Protecting and Accessing Data from the Survey of Earned Doctorates: A Workshop Summary - National Research Council (The National Academies Press, 2010)
The Survey of Earned Doctorates (SED) collects data on the number and characteristics of individuals receiving research doctoral degrees from all accredited U.S. institutions. The results of this annual survey are used to assess characteristics and trends in doctorate education and degrees. This information is vital for education and labor force planners and researchers in the federal government and in academia.
Keywords: Education; Computers and Information Technology; Behavioral and Social Sciences; Surveys and Statistics

Guidebook of Practices for Improving Environmental Performance at Small Airports - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2010)
TRB’s Airport Cooperative Research Program (ACRP) Report 43: Guidebook of Practices for Improving Environmental Performance at Small Airports outlines federal environmental regulations and requirements, and identifies activities in which airport operators can be proactive in promoting environmental stewardship.As a quick reference, summary graphics provide information pertaining to the cost and savings as well as the necessary knowledge and amount of time to implement a particular activity. In addition, there are five case studies that discuss environmental initiatives already undertaken at airports that can serve as a guide for other airports.The report includes the collection of environmental stewardship practices in a searchable, filterable spreadsheet format on a CD-ROM, which is packaged with the report.The CD-ROM included as part of ACRP Report 43 is also available for download from TRB’s website as an ISO image. Links to the ISO image and instructions for burning a CD-ROM from an ISO image are provided below.Help on Burning an .ISO CD-ROM ImageDownload the .ISO CD-ROM Image(Warning: This is a large file that may take some time to download using a high-speed connection.)CD-ROM Disclaimer - This software is offered as is, without warranty or promise of support of any kind either expressed or implied. Under no circumstance will the National Academy of Sciences or the Transportation Research Board (collectively “TRB’) be liable for any loss or damage caused by the installation or operations of this product. TRB makes no representation or warrant of any kind, expressed or implied, in fact or in law, including without limitation, the warranty of merchantability or the warranty of fitness for a particular purpose, and shall not in any case be liable for any consequential or special damages.Errata1) ACRP Report 43 contained incorrect information in Figure 2. The corrected version of Figure 2 is available online in PDF format.2) On page 18 of the print version of the report the first two lines of text were inadvertently omitted. The online version of the report has been corrected.
Keywords: Transportation and Infrastructure

Improving Health Care Cost Projections for the Medicare Population: Summary of a Workshop - National Research Council (The National Academies Press, 2010)
Developing credible short-term and long-term projections of Medicare health care costs is critical for public- and private-sector policy planning, but faces challenges and uncertainties. There is uncertainty not only in the underlying economic and demographic assumptions used in projection models, but also in what a policy modeler assumes about future changes in the health status of the population and the factors affecting health status , the extent and pace of scientific and technological breakthroughs in medical care, the preferences of the population for particular kinds of care, the likelihood that policy makers will alter current law and regulations, and how each of these factors relates to health care costs for the elderly population.
Keywords: Health and Medicine; Behavioral and Social Sciences; Surveys and Statistics

The Healthcare Imperative: Lowering Costs and Improving Outcomes: Workshop Series Summary - Institute of Medicine (The National Academies Press, 2010)
The United States has the highest per capita spending on health care of any industrialized nation but continually lags behind other nations in health care outcomes including life expectancy and infant mortality. National health expenditures are projected to exceed $2.5 trillion in 2009. Given healthcare's direct impact on the economy, there is a critical need to control health care spending.
Keywords: Health and Medicine

Clinical Data as the Basic Staple of Health Learning: Creating and Protecting a Public Good: Workshop Summary - Institute of Medicine (The National Academies Press, 2010)
Successful development of clinical data as an engine for knowledge generation has the potential to transform health and health care in America. As part of its Learning Health System Series, the Roundtable on Value & Science-Driven Health Care hosted a workshop to discuss expanding the access to and use of clinical data as a foundation for care improvement.
Keywords: Health and Medicine